Interpretation of illness in cancer survivors is associated with health-related variables and adaptive coping styles - Fischer Julia; Büssing Arndt (BMC, 2009)
Abstract Background A patient's interpretation of illness may have an influence on the choice of coping strategies and decision making. We intended to analyze the meaning German cancer survivors would attribute to their disease, and investigated intercorrelations between the respective interpretations, health-related variables and adaptive coping strategies. Methods In an anonymous cross-sectional survey, we analyzed the interpretations of disease (according to Lipowski's eight 'meaning of illness' categories) in 387 patients with cancer (81% breast cancer). To make statements about their conceptual relationships with health-related variables, we correlated the 8 items of the 'Interpretation of Illness' questionnaire (IIQ) with health-related quality of life, anxiety/depression, fatigue, life satisfaction, and adaptive coping strategies. Results Most cancer survivors regarded their disease as a challenge (52%), others as value (38%) or even an interruption of life (irreparable loss; 35%); weakness/failure (5%) and punishment (3%) were rated the lowest. The fatalistic negative interpretations 'interruption/loss' and 'enemy/threat' were inversely correlated with mental health-related quality of life and life satisfaction, and positively with an escape-avoidance strategy, depression and anxiety. In contrast, positive disease interpretations (i.e., 'challenge' and 'value') correlated only with adaptive coping strategies. Physical health correlated with none of the disease interpretations. Conclusion Despite conceptual limitations, the 8-item schema could be regarded as a useful screening approach to identify patients at risk for reduced psychosocial functioning.